Event storming (O'Reilly Media, 2019)
"More and more, Allen Holub (Holub Associates) has come to see event storming as a critically important tool in the architect's palate. It's a way to simultaneously collaborate with businesspeople to understand the problems that the business has to solve and develop an architecture for the solution. Join Allen for an in-depth look at event storming and its underlying concepts (from DDD), as well as an extensive hands-on demo of the process. Along the way, you'll discover the entities, bounded contexts, and events that are essential for an effective choreographed microservice (or reactive) architecture. You'll come away from this talk with a solid understanding of how event storming works and how to apply it."--Resource description page